Unchained Russia - Russell, Charles Edward 1860-1941 (Slavica, 2021)
"Charles Edward Russell was a major intellectual and political figure of the late nineteenth- and early twentieth-century United States. As a very well-known American radical, he published many books on the US economy, the condition of workers, social issues, and other subjects. He was an active member of the American socialist movement before 1917, but when the US entered the war in 1917 he moved to support the US war effort, something many radicals had still opposed. When President Woodrow Wilson was preparing a special delegation to Russia in the summer of 1917, he added Russell to the delegation in an effort to include a radical at a time when the Russian Provisional Government was increasingly socialist. Russell was the only delegation member to write an account of his trip, and he hurried to get it published by early 1918. He managed to communicate the complexity of the situation in 1917 Russia and inform readers about some of the leaders who were not well recognized abroad. He provided an optimistic view of the revolution, Russia's future, and how it might have a significant positive effect on change in the United States and elsewhere."
Includes bibliographical references and index
Keywords: Oktoberrevolution; United States / Special Diplomatic Mission to Russia; Soviet Union / Social conditions; Soviet Union / History / Revolution, 1917-1921; Erlebnisbericht